Jurnal Vokasi MODEL IMPLEMENTASI KEBIJAKAN PENYELENGGARAAN KEPARIWISTAAN: Usaha Perjalanan Wisata - Putri Mutiara Rakista; Chandra Gunawan (Acitya Politeknik Bisnis Mayasari, 2022)
The implementation of tourism is the main driving element of tourism activities that are formulated in such a way as to aim for national development. The title is motivated because the management of tourism objects under government control still encountersseveral obstacles such as lack of maintenance efforts, there are tourist objects that are not facilitated, then many tourist objects are in dirty condition and do not guarantee safety for tourists. The purpose of this research is to create a model for implementing the implementation of tourism policies. The research method used in this study uses a literature review approach (literature review). the results of the study resulted in a model for implementing tourism implementation policies that refer to two aspects, namely aspects of policy implementation and environmental aspects. In accordance with the literal analysis, these aspects are considered to be the most influential in the successful implementation of tourism implementation policies.